The sustainable transport pathway: A holistic strategy of Five Transformations - Becky Loo; Ka Ho Tsoi (Journal of Transport and Land Use)
In this paper, a holistic strategy of the “Five Transformations” is introduced to offer a comprehensive and synergetic theory to tackle various daunting challenges faced by the transport sector and ultimately pave the way to sustainable transport. The Five Transformations span across city development, the economy, vehicle technology, modal-split and lifestyles at various geographical scales. Building on the current literature and empirical evidence, this paper advocates for fundamental changes in all aspects of the society beyond transportation. To move forward, this paper scrutinizes the association between land-use planning and the Five Transformations. It is clear that land-use policies are important drivers in implementing and reinforcing the policy instruments under the Five Transformations.